Impact of Social Media Marketing on Impulsive Buying Behavior: The Mediating Role of Hedonic Motivation - Putra, Furqhan Chaesar Mandala; Putra, Setiawan Mandala; Raheni, Cahyaning (Jurnal Mebis, 2025)
The rapid development of social media platforms, such as TikTok, has transformed the way companies market their products and interact with consumers. Social media has evolved beyond a promotional tool into a space capable of evoking emotions and stimulating spontaneous purchasing behaviours in consumers. This study aims to analyse the effect of Social Media Marketing (SMM) on Impulsive Buying (IB), with Hedonic Shopping Motivation (HSM) serving as a mediating variable. A quantitative approach was employed using a survey method involving 150 active social media users from Palu City, Indonesia. Data were analysed using Partial Least Squares structural equation modelling (PLS-SEM) through the SmartPLS application. The results reveal that social media marketing has a positive and significant effect on both hedonic shopping motivation and impulsive buying. Moreover, hedonic shopping motivation exerts a positive influence on impulsive buying and serves as a partial mediator in the relationship between social media marketing and impulsive buying. These findings emphasise that the more effective social media marketing strategies are in creating enjoyable shopping experiences, the higher the consumers’ tendency to engage in impulsive purchasing behaviour. This study contributes to a deeper understanding of the role of hedonic motivation in consumer purchasing behaviour in the digital era and provides practical implications for marketers to design social media content that stimulates emotional experiences and enhances spontaneous buying impulses.